Gut Microbiota and Its Impact on Brain Function and Mental Health - Wójcik, Zofia Martyna; Kamińska-Omasta, Katarzyna; Omasta, Bartosz; Krupa, Olga; Pietrukaniec, Paulina Dorota; Romańczuk, Kuba Borys; Furtak, Kinga; Stolarczyk, Szymon Przemysław; Czerska, Magdalena Agata; Rybak, Daria (Quality in Sport, 2025)
The intestinal microbiota is a complex ecosystem playing a crucial role in maintaining human homeostasis. It consists of billions of microorganisms, including bacteria, viruses, fungi, and archaea, which closely interact with their host. Recent research reveals that microbiota not only supports metabolic and immune functions but also influences central nervous system (CNS) regulation via the gut-brain axis, a two-way communication system. The gut-brain axis modulates neurotransmitter production (e.g., serotonin, GABA), immune responses, and interacts through bacterial metabolites. Dysbiosis, or microbiota imbalance, is linked to neuropsychiatric disorders like depression, anxiety, and autism. Maintaining microbiota balance is essential for mental health. This paper reviews literature on the impact of gut microbiota on mental health, focusing on gut-brain axis mechanisms, diet, and therapeutic potential. These findings are especially relevant for personalized medicine approaches targeting microbiota to manage mental disorders.